Lipopolysaccharide-induced suppressor cells for delayed-type hypersensitivity to herpes simplex virus: nature of suppressor cell and effect on pathogenesis of herpes simplex. - Altmann, D M (1984)
Treatment of mice with LPS at the time of priming with herpes simplex virus type 1 (HSV1) causes the preferential activation of virus-specific T suppressor (Ts) cells. These Ts cells can transfer suppression to the efferent limb of a DTH response. Priming under these conditions is associated with enhanced cell-recruitment to the inoculation site, but had no effect on virus clearance. The induction of suppression was abrogated by pretreatment of mice with cyclophosphamide or indomethacin. LPS had no effect on the antibody response to HSV1 during acute infection, although treated mice showed a raised antibody titre one month after inoculation. Susceptible mice inoculated with HSV1 and given LPS showed protection, both from lethal herpes encephalitis and from demyelination within the CNS as reflected by ear paralysis. These results imply that, during some stages of acute infection, T cell effector mechanisms may themselves mediate tissue damage. At such times, Ts cells may perform a beneficial role leading to a reduction in pathology.